Cryptocurrency Contagion: How Does It Differ From the Commodity Contagion? - Handika, Rangga (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
Given the recent substantial increase in market capitalization of bitcoin (BTC) and oil, both of them are considered alternative investments and could affect the traditional financial markets. This study compares the contagions between bitcoin (BTC) and oil to major American, European, and Asian equity markets. The contagion analysis follows the procedures from Forbes and Rigobon (2002) in analyzing the jumps in the correlation coefficients and suggests a new idea by extracting and evaluating the idiosyncratic components. The idiosyncratic part refers to the unique series after filtering the common/global part. Analyzing this part allows us to prevent bias due to global factors. This novelty analysis extends previous studies by filtering the common factor. Thus, allowing us to thoroughly investigate specific country. Using the daily return series from January 1, 2016, to January 1, 2024 (downloaded from the investing website), I document that both BTC and oil transmit contagion to the major equity markets, albeit in different directions. BTC (oil) tends to trigger positive (negative) contagion. The results are consistent regardless of whether the daily return or idiosyncratic series are used and when the correlations are adjusted for heteroskedasticity.